Effect of KNO3 Concentration and Fruit Maturity Levelon the Viability of Papaya Seed (Carica papayaL.) cv.Callina - pamungkas, wahyu widi kusuma; Kusmiyati, Florentina; Karno, Karno (Journal of Tropical Crop Science and Technology, 2020)
The research was aimed to examine the effect of different concentration of KNO3 and fruit maturity level on the seed viability of papaya. This research used Completely Randomized Design (CRD) factorial with two main treatments. The first treatment was fruit maturity level (A0: 75% dan A1: 100%). The second treatment was concentration of KNO3 (B1 = 0 M ; B2 = 0,05 M ; B3 = 0,1 M ; B4 = 0,15 M ; B5 = 0,2 M). Seedling parameters observed were germination rate, seed growth rate, vigour index, and maximum growth potential. Nursery parameters observed were plant height and leaf area. Data were analyzed with Analysis of Variance (ANOVA) followed by Duncan Multiple Range Test (DMRT) at 5%. The interaction between fruit maturity and KNO3 concentration showed significantly in germination rate, seed growth rate, vigour index, maximum growth potential and plant height. Leaf area were onlyaffected by KNO3 concentration. This showed that fruit maturity level and KNO3 concentration were significantly affects seed viability.